Adherence to the European Society of Cardiology hypertension guidelines over 12 years of follow-up in the Irish population - Sexton, Donal; Scarlett, Siobhan; Briggs, Robert; Kenny, Rose (My University, 2026)
Background: Hypertension is a significant risk factor for cardiovascular disease, dementia and chronic kidney disease (CKD). Older adults bear the brunt of these conditions, and managing hypertension can be especially challenging in this cohort. In this study, we apply the European Society of Cardiology (ESC) hypertension guidelines to adults ≥50 years participating in a nationally-representative longitudinal study on ageing, providing crucial context for guideline implementation among older adults. Methods: Data from waves 1 (2009-2010), 3 (2014-2015) and 6 (2021-2023) of The Irish Longitudinal Study on Ageing were analysed. Hypertension (blood pressure (BP) ≥140/90 mm Hg) prevalence, awareness, treatment, control (on-treatment BP <130/80 mm Hg) and adherence to ESC recommendations were assessed. Subgroup analyses included people aged ≥85 years, adults with frailty, with CKD and with home BP measurements. Data were analysed using Stata V.15.1 applying inverse probability weighting. Results: From wave 3 (n=5329), weighted hypertension prevalence was 64.0% (62.4-65.6%). Of these, 55.5% were aware and 70.3% were on antihypertensive treatment. 32.2% on treatment had controlled BP, 20.9% were on dual therapy and 55.2% were taking one ESC-recommended agent. 87.8%, 77.1% and 76.7% of those with hypertension at waves 1, 3 and 6 were undiagnosed, untreated or uncontrolled. Hypertension prevalence was 91.1% (84.7-95.0%) in people ≥85 years and 75.9% (69.3-81.5%) in moderate-severe frailty. Conclusions: In a nationally-representative sample of older Irish adults, there is a high prevalence of hypertension, with low awareness, control and adherence to ESC guidelines.
PUBLISHED
Keywords: Delivery of Health Care; Epidemiology; Global Burden of Disease; Hypertension; Ageing; Ageing, memory and other cognitive processes; Cardiovascular Diseases; Cardiovascular regulation and hypertension; Chronic Kidney Disease; Epidemiology